Stress hyperglycemia in acute myocardial infarction - Koraćević Goran; Vasiljević Sladjana; Veličković-Radovanović‡ Radmila; Sakač Dejan; Obradović Slobodan; Damjanović Miodrag; Krstić Nebojša; Zdravković Marija; Kostić Tomislav (Vojnosanitetski Pregled)
nema